DESAIN BAHAN AJAR BERBASIS AKTIVITAS PENALARAN MATEMATIS MENGGUNAKAN MODEL MISSOURI MATHEMATIC PROJECT MATA KULIAH ANALISIS KOMPLEKS - Nuraina Nuraina; Muliana Muliana; Mursalin Mursalin; Mila Kartika Sari Bangun; Ucuk Puji Rahayu (Program Studi Pendidikan Matematika, Universitas Bina Bangsa Getsempena, 2022)
The failure of students in studying complex analysis courses is based on student learning habits that only focus on memorizing concepts from the material studied without understanding it properly, and lack of motivation to repeat the material that has been studied. The teaching materials used in this course are textbooks. However, the textbook used still does not contain activities for students' mathematical reasoning abilities, students cannot learn independently from the book, because the material presented is difficult to understand, even lecturers who teach this complex analysis course have to redesign the material, writing in written form. hand is then given to the student. One effort that could be to improve students' mathematical reasoning abilities is to facilitate learning resources with supporting teaching materials. In this study, teaching materials will be designed based on mathematical reasoning activities using the Missauri Mathematical Project (MMP) learning model. The research method used in this research is the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. The development of complex analysis textbooks based on reasoning activities using the Missauri Mathematical Project learning model is feasible to be developed with the percentage of assessment by media expert validators obtained an average score of 91.79% in the